Meningkatkan Kemampuan Komunikasi Melalui Public Speaking Anggota BUMDes Wargaluyu, Arjasari -Bandung - Yulia Sariwaty; Dini Rahmawati; Diny Fitriawati (Pengelola Jurnal Politeknik Negeri Ketapang, 2023)
Communication plays an important role in human relations. Through communication messages and ideas can be conveyed between humans to one another. Public speaking is a skill in communicating in public, which is very useful and must be owned by all parties to support self-confidence as well as develop and enhance a wide network of relationships. The inability to convey messages, ideas and ideas, coupled with the lack of confidence from BUMDes members and youth youth members is the reason behind holding public speaking training. The stages of the training activities were preceded by a pre-test to determine the participant's speaking ability and level of confidence. Submission of the theory of public speaking is carried out as a basis for the provision of knowledge and knowledge of the participants. Practice is a means of practicing skills after gaining knowledge, techniques and tips. The last post-test as an evaluation process of the results of the training. The training received positive responses and appreciation from the participants, the post-test results also showed an increase in the participants' speaking skills and self-confidence after receiving provision of knowledge and knowledge about public speaking.